TOURISM EQUATION: CULTURAL TOURISM MARKETING STRATEGY BADUY TRIBE IN LEBAK DISTRICT - Eka Prasetiawan; Dudi Permana; Arrisetyanto Nugroho (Dinasti Publisher, 2020)
Baduy Tribe Village is one of the famous tourist destinations in the Lebak Regency. As a major tourist destination, the number of tourists visiting the Baduy Tribe Village is still far from expectations. That is because the tourism marketing strategy is still not optimal by the Regional Government of Lebak Regency. This research uses a qualitative method approach by utilizing the literature review and previous experience. One alternative strategy is through the creation of a Tourism Equation that utilizes tourist attractions visited by many tourists, such as Sawarna Beach tourism or other tourist attractions in other areas. The storefront of tourism can trigger public interest to further visit the Baduy Tribe Village. The results of this paper are expected to be used as an alternative that can be tried by the Regional Government of the Regency of Lebak to improve tourism development in the Regency of Lebak.